Laparoscopía de un absceso gigante intraabdominal. Reporte de caso posparto inmediato (2018)
The intra-abdominal abscess is an emergency surgical pathological condition, result of frequent complication of appendicitis difficult to diagnose. Within the clinical manifestations, there is abdominal pain, elevation ends in spikes and a systemic inflammatory response. We present the unusual clinical case in the midst of a patient of 18 years, with a gestational age of 37.4 weeks, who consulted for abdominal pain and urinary symptomatology. It is managed as an infection of the urinary tract, the pain is increased and triggers uterine activity and normal delivery; with permanence of pain, fever and mass sensation. Imaging is a giant intra-abdominal abscess, which is why it is taken to laparoscopic surgery with successful subsequent drainage of intra-abdominal abscess, with satisfactory evolution. It is important to emphasize the early diagnosis of acute appendicitis during pregnancy, taking into account the clinical and the relationship of the symptoms that occur during pregnancy. The objective of this case is to make known the relevance of implementing laparoscopicsurgery in the management of intra-abdominal abscesses, to evidence the advantages as a method of surgical treatment, and the least trauma for the patient. © 2018, Sociedad Argentina de Gastroenterologia. All rights reserved.